De Manila al continente asiático: riesgos y experiencias de las misiones católicas en el siglo XVII - Tomás A. Mantecón (E-Spania)
This research analyses the perceptions of the Catholic mission projected from Manila to the Asian coasts. The empirical material corresponds to what can be labeled as minor chronicles (informal reports writen by missionaires). This article offers an explanation integrating both the missionary projects and experiences and perceptions writen by the protagonists themselves so that it emerges a singular information that integrates projects, interests and emotions to offer a human vision of the missions. There is also an evaluation of the missions concretions and results, characterizing the zones of interaction and cultural adhesions between the Europeans and Asian societies and, thus, the building of cultural hybridation as a result of the mutual inculturation.